Molecular screening of Plasmodium sp. asymptomatic carriers among transfusion centers from Brazilian Amazon region Triagem molecular de portadores assintomáticos de Plasmodium sp. entre Bancos de Sangue da região Amazônica brasileira - Érica Fugikaha; Patrícia Aparecida Fornazari; Roberta de Souza Rodrigues Penhalbel; Alexandre Lorenzetti; Roberto Duarte Maroso; Juvanete Távora Amoras; Ana Sueli Saraiva; Rita Uchôa da Silva; Cláudia Regina Bonini-Domingos; Luiz Carlos de Mattos; Andréa Regina Baptista Rossit; Carlos Eugênio Cavasini; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
The transmission of malaria in Brazil is heterogeneous throughout endemic areas and the presence of asymptomatic Plasmodium sp. carriers (APCs) in the Brazilian Amazon has already been demonstrated. Malaria screening in blood banks is based on the selection of donors in respect to possible risks associated with travel or residence, clinical evidence and/or inaccurate diagnostic methods thereby increasing the probability of transfusion-transmitted infection. We evaluated the frequency of APCs in four blood services in distinct areas of the Brazilian Amazon region. DNA was obtained from 400 human blood samples for testing using the phenol-chloroform method followed by a nested-PCR protocol with species-specific primers. The positivity rate varied from 1 to 3% of blood donors from the four areas with an average of 2.3%. All positive individuals had mixed infections for Plasmodium vivax and Plasmodium falciparum. No significant differences in the results were detected among these areas; the majority of cases originated from the transfusion centres of Porto Velho, Rondônia State and Macapá, Amapá State. Although it is still unclear whether APC individuals may act as reservoirs of the parasite, efficient screening of APCs and malaria patients in Brazilian blood services from endemic areas needs to be improved. A transmissão da malária no Brasil é heterogênea em todas as áreas endêmicas e a presença de portadores assintomáticos de Plasmodium sp. (PAPs) na Amazônia brasileira já foi demonstrada. A triagem de pacientes maláricos em bancos de sangue é baseada na seleção dos doadores com relação aos riscos possíveis associados com residência, evidência clínica e/ou os métodos diagnósticos não acurados que aumentam a probabilidade da infecção transmitida por transfusão. Avaliamos a freqüência de PAPs em quatro bancos de sangue em áreas distintas da região Amazônica brasileira. O DNA foi obtido a partir de 400 amostras de sangue humano usando o método do fenol-clorofórmio, seguido por um protocolo de nested-PCR com oligonucleotídeos espécie-específicos. A taxa de positividade variou de 1 a 3% de doadores do sangue das quatro áreas, com uma média de 2,3%. Todos os indivíduos positivos tinham infecções mistas entre o Plasmodium vivax e o Plasmodium falciparum. Nenhuma diferença significativa nos resultados foi detectada entre estas áreas; a maioria dos casos originou dos Hemocentros de Porto Velho, do Estado de Rondônia e de Macapá, Estado do Amapá. Embora ainda não esteja claro se os indivíduos PAPs possam agir como reservatórios do parasito, a triagem eficiente de PAPs e de pacientes com malária em bancos de sangue no Brasil das áreas endêmicas necessita ser implementada.